IDEOLOGI POLITIK PRESIDEN TERPILIH 2019 MODEL NORMAN FAIRCLOUGH - Ramadhan Muhtar; Jufri Jufri; Andi Sukri (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2022)
This study aims to: (1) Reveal the experiential value of the political news texts of the 2019 elected President and Vice President of the Republic of Indonesia. (2) Reveal the relational value of the political news texts of the 2019 elected President and Vice President of the Republic of Indonesia. politics of the 2019 RI Elected President and Vice President. The data for this research are words, clauses, and sentences contained in the 2019 Elected President news, especially reporting on the elected president's policies. The data sources in this study are the online media Kompas.com and Detik.com. The data collection techniques used are documentation techniques, library techniques, and note-taking techniques. The results of the research show that: (1) Political ideology based on experiential value found metaphors, meaning relations, hyponymy, nominalization, and passivity. (2) Political ideology based on relational values is found in formal words, informal words, declarative sentence mode, interrogative sentence mode, positive evaluation, and negative evaluation. (3) Political ideology based on expressive values found intentional modality.